MASALAH SYARAT AWAL DAN SYARAT BATAS UNTUK KONDUKSI PANAS DALAM SILINDER PANJANG - , SEPTIAN HERTOTO MAMBRASAR ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The IBVP for the heat conduction in long cylinders consists of heat conduction equation, initial condition and boundary condition. Heat conduction equation in cylinders describes heat distribution in solid and hollow cylinder over time. The discussion in this Bachelor Thesis starts from Besselâs equation, Bessel function, and Fourier-Bessel series which is used to solve heat conduction problem in cylinders. Then, we discuss about the heat conduction equation modelling, some variation of homogeneous IBVP and nonhomogeneous IBVP. We discuss only nonhomogenous IBVP which the heat source and nonhomogeneous boundary condition do not depend on time. Homogeneous IBVP is solved by method of separation of variables and nonhomogeneous IBVP is solved by splitting the problem up into steady-state problem and transient problem.